Close binaries and common envelopes. Issue 3 (1st June 2020) - Jones, David; García-Rojas, Jorge; Pejcha, Ondřej; Wesson, Roger
Abstract : David Jones, Jorge García-Rojas, Ondřej Pejcha and Roger Wesson report on their RAS Specialist Discussion Meeting exploring "Common envelope evolution and post-common-envelope systems". Abstract: David Jones, Jorge García-Rojas, Ondřej Pejcha and Roger Wesson report on their RAS Specialist Discussion Meeting exploring "Common envelope evolution and post-common-envelope systems".